The production of supercapacitor carbon electrodes based on sugar palm fronds using chemical and physical activation combination - Awitdrus Awitdrus; Decha Apriliany Suwandi; Agustino Agustino; Erman Taer; Rakhmawati Farma (Journal of Aceh Physics Society, 2021)
Abstrak. Pembuatan elektroda karbon superkapasitor berbasis limbah pelepah aren dengan kombinasi pengaktifan kimia dan fisika telah berhasil dilakukan. Aktivasi kimia dilakukan dengan menggunakan agen pengaktif 0,3 M KOH dan aktivasi fisika menggunakan gas CO2 pada suhu 900oC selama 2,5 jam. Karakterisasi sifat fisis elektroda meliputi susut massa, tebal, diameter, densitas dan derajat kristalinitas. Karakterisasi sifat elektrokimia elektroda dilakukan dengan menggunakan metode siklis voltametri. Setelah proses karbonisasi-aktivasi fisika, massa, tebal, diameter dan densitas elektroda mengalami penurunan persentase masing-masing adalah 60,87; 30,43; 24,08 dan 5,71%. Elektroda PA-0,3 memiliki struktur semi kristalin, yang ditandai dengan adanya dua puncak yang lebar pada sudut hamburan sekitar 25o dan 46o. kapasitansi spesifik elektroda PA-0,3 berdasarkan variasi laju pemindaian  adalah 90 F g-1 untuk 1 mV s-1, 82 F g-1 untuk 2 mV s-1, dan 71 F g-1 untuk 5 mV s-1. Abstract. The production of supercapacitor carbon electrodes based on sugar palm frond waste using chemical and physical activation combinations have been successfully carried out. The chemical activation was carried out using 0.3 M KOH activating agent and the physical activation using CO2 gas at a temperature of 900oC for 2.5 h. Characterization of the physical properties of the electrodes includes mass loss, thickness, diameter, density and degree of crystallinity. The electrochemical properties characterization of the electrodes was carried out using the cyclic voltammetry method. After the carbonization-physical activation process, the mass, thickness, diameter, and density of the electrodes decreased in the percentage of 60.87, 30.43, 24.08, and 5.71%, respectively. The PA-0.3 electrode has a semi crystalline structure, which characterized by the presence of two broadening peaks at a scattering angle around of 25o and 46o. The specific capacitance of the PA-0.3 electrode based on the scan rate variations is 90 F g-1 for 1 mV s-1, 82 F g-1 for 2 mV s-1, and 71 F g-1 for 5 mV s-1.Keywords: Sugar palm fronds, Chemical activation, Physical activation, Carbon electrode, Supercapacitor